Memory at the Sharp End: The Costs of Remembering With Others in Forensic Contexts. (2nd August 2018) - Hope, Lorraine; Gabbert, Fiona
Abstract: In many applied contexts where accurate and reliable information informs operational decision‐making, emergency response resource allocation, efficient investigation, judicial process, and, ultimately, the delivery of justice, the costs of unfettered conversational remembering can be high. To date, research has demonstrated that conversations between co‐witnesses in the immediate aftermath of witnessed events and co‐witness retellings of witnessed events often impair both the quality and quantity of information reported subsequently. Given the largely negative impact of conversational remembering on the recall of both individual witnesses and groups of witnesses in this context, this review explores the reasons why these costs occur, the conditions under which costs are exacerbated, and how, in practical terms, the costs can be reduced in order to maximize the accuracy and completeness of witness accounts. Abstract : Hope and Gabbert review and distil the relevant research examining the mnemonic consequences associated with conversations within an eyewitness context. In particular, they focus on how co‐witnesses' retellings of witnessed events impair the quantity and quality of information subsequently reported to law enforcement authorities. Notably, they also provide interventions (e.g., careful witness management and post incident procedures, use of warnings, early individual accounts, etc.) to mitigate these negative, well‐documented mnemonic effects.